Group Exhibition-Art Athina, The Collection Gallery, Palaio Faliro - Antoniou, Klitsa (My University, 2026)
Art Athina, The Collection Gallery, Palaio Faliro, Greece Atlantropa Series But the Sea Kept Turning Blank Pages Looking for History